Comparison of Metformin Versus Repaglinide Monotherapy in the Treatment of New-Onset Type 2 Diabetes Mellitus - Ahmad, Waseem; Khan, Shahzad Alam; Sajid, Muhammad; Safdar, Sohail; Khan, Ambreen Nadeem (Biological and Clinical Sciences Research Journal, 2025)
Poorly controlled diabetes has devastating effects on the heart, kidneys, eyes, nerves, and blood vessels. This study aimed to compare mean HbA1c values after 3 months of initiating metformin versus repaglinide monotherapy in treating new-onset type 2 diabetes mellitus. Methods: This open-label, parallel-group, randomized controlled trial was conducted at the Department of Medicine, Nishtar Hospital, Multan, from 1st February 2025 to 31st May 2025. Sixty newly diagnosed T2DM patients aged 20–60 years were enrolled after informed consent. Baseline HbA1c was measured, and patients were randomly assigned using a lottery method with sealed opaque envelopes. Group A received Repaglinide monotherapy (0.75–1.5 mg/day), and Group B used Metformin (750–1500 mg/day). Serum sugar was monitored daily and doses adjusted in the first week. All patients received diet and lifestyle advice with monthly follow-up for three months. Compliance was monitored with a checklist. HbA1c was measured again at three months. Data was analysed through SPSS version 23. Mean HbA1c between the groups was compared using a t-test at the 5% significance level. Results: The mean age was 51.8±6.6 years, and 60% were male. Obesity, smoking, and hypertension were found in 51.7%, 41.7%, and 70% respectively. Mean HbA1c decreased from 8.4 ± 0.5 to 6.1 ± 0.6. The Repaglinide group had higher baseline HbA1c but lower post-treatment HbA1c (5.6 ± 0.3 vs. 6.6 ± 0.3, p-value < 0.01) than the Metformin group. Conclusion: Repaglinide monotherapy was more effective than Metformin in reducing HbA1c over three months, supporting use in early T2DM management.